Mathématiques
liliyassou93
39

Résoudre les équations 3 (2x-5)=5- (3x-7) -3(2x-4)=5x+3(rac.carr)7 (-4x-3)(5x+2)=0 (2x-3)(4+7x)+(2x-3)(x+4)=0 3x(carré)-2x=7x (5x-7)(-3x+2)=(-3x+2)(2x-5) X(carré)=25 X(carré)+4x=-4 Merci bcp

+3
(1) Réponses
matilde

bonjour 3 (2x-5)=5- (3x-7)⇔ 6x-15=5-3x+7 ⇔9x=27 ⇔x=3 -3(2x-4)=5x+3√7 ⇔ -6x+12=5x+3√7 ⇔11x=12-3√7 ⇔ x=12/11-3√7/11 (-4x-3)(5x+2)=0 ⇔-4x-3=0 ou 5x+2=0 ⇔x=-3/4 ou x=-2/5 (2x-3)(4+7x)+(2x-3)(x+4)=0 ⇔ (2x-3)(4+7x+x+4)=0 ⇔(2x-3)(8x+8)=0 ⇔8(2x-3)(x+1)=0 ⇔ 2x-3=0 ou x+1=0 ⇔x=3/2 ou x=-1 3x²-2x=7x ⇔ 3x²-9x=0 ⇔3x(x-3)=0 ⇔x=0 ou x=3 (5x-7)(-3x+2)=(-3x+2)(2x-5) ⇔ (-3x+2)(5x-7-2x+5)=0 ⇔-(3x-2)(3x-2)=0 ⇔-(3x-2)²=0 ⇔3x-2=0 ⇔x=2/3 x²=25 ⇔ (x+5)(x-5)=0 ⇔x=5 ou x=-5 x²+4x=-4 ⇔ x²+4x+4=0 ⇔(x+2)²=0 ⇔x=-2

Ajouter une réponse